Deplatforming the Classroom: Fostering Gen Alpha Students’ Autonomy and Self-Reliance Through Project-Based Tactile Learning - Khalid Al-Madani; Rizal Sulthon; Maskur Maskur (Education and Sociedad Journal, 2026)
This study examines the strengthening of self-reliance among Gen Alpha students at Islamic elementery school within the context of increasing digital dependency. This investigation is crucial as pervasive digital dependency increasingly erodes this generation's real-world problem-solving skills and cognitive autonomy, demanding urgent pedagogical intervention. Employing a qualitative case study design, data were gathered via non-participant observations and in-depth interviews with 14 students, 4 teachers, and 2 instructors, then analyzed using thematic analysis. The findings reveal that students’ self-reliance is not developed through instructional approaches alone, but through experiential learning integrated into daily routines and structured habituation. The findings reveal that students’ self-reliance is not developed through instructional approaches alone, but through experiential learning integrated into daily routines and structured habituation. Independence is manifested holistically across cognitive, emotional, social, and spiritual dimensions through practices such as collective rituals, time-structured discipline, micro-social discipline, and out-of-class activities. The study further shows that digital dependency is not an inherent trait but a socially constructed condition that can be reduced through pedagogical design. Strategies such as experiential learning, detachment from parental dependency, and project-based learning contribute to behavioral transformation from dependency to autonomy. This research contributes a conceptual model of contextual self-reliance based on pesantren-school culture, emphasizing habituation, social interaction, and experiential engagement as key elements. It suggests that fostering independence in the digital era requires reconstructing learning environments rather than merely restricting technology use.